Diferenciacija in standardi znanja v učniku za slovenščino - Saksida, Igor (Jezik in slovstvo, 1997)
The term differentiation is both in Slovene and foreign literature understood in different ways; consequently, the multi-level teaching process may mean very different types of differentiation, from external to internal and flexible. The article sums up basic theoretical premises and - bringing them together with the existing legislation and the concept of the primary school renovation - suggests models for individualization in the first three-year period, for flexible differentiation in the second three-year period, and for external differentiation in the thirs three-year period.
Keywords: Slovene; slovenščina; pouk; prenova; učni načrti; učni programi; učna diferenciacija